2020
DOI: 10.1007/s00268-020-05862-y
|View full text |Cite
|
Sign up to set email alerts
|

Indications and Outcomes for Non‐Trauma Emergency Laparotomy: A Comparison of Rwanda, South Africa, and the USA

Abstract: Background Emergency conditions requiring exploratory laparotomy (EL) can be challenging. The objective of this study is to describe indications, outcomes, and risk factors for perioperative mortality (POMR) after non‐trauma EL. Methods This was a prospective study of patients undergoing non‐trauma EL at four hospitals in Rwanda, South Africa, and the USA. Multivariate logistic regression was used to determine factors associated with POMR. Results Over one year, there were 632 EL with the most common indicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
11
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 38 publications
6
11
1
Order By: Relevance
“…Male predominance (male to female ratio = 1.4:1) was observed in this study which is in agreement with other studies in Africa, and even in the developed world [12,13,18,19]. The mean age was 47.4 years which is comparable with findings in South Africa reported by Rickard et al [8], in the USA reported by Purcell et al in Malawi [16]. However, this age is much older than findings from other studies in Africa [10,11,20].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Male predominance (male to female ratio = 1.4:1) was observed in this study which is in agreement with other studies in Africa, and even in the developed world [12,13,18,19]. The mean age was 47.4 years which is comparable with findings in South Africa reported by Rickard et al [8], in the USA reported by Purcell et al in Malawi [16]. However, this age is much older than findings from other studies in Africa [10,11,20].…”
Section: Discussionsupporting
confidence: 93%
“…The indications and outcomes of emergency abdominal surgery vary within different settings from high, middle to low-income countries [8]. A study in Russia revealed acute appendicitis, acute cholecystitis, and acute pancreatitis as the most common abdominal surgical emergencies [9].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Around 175,000 laparotomies are performed annually in the USA and around 30,000 to 50,000 emergency laparotomies are performed annually in the UK with a variety of surgical etiologies 4,5 . The laparotomy is also a frequent MP-2023-792 intervention in limited resources countries in sub-Saharan Africa, where more than half of the surgical procedures performed are emergency laparotomies with high perioperative mortality rates 6 . More often laparotomy is the only way to determine the underlying pathology, the anatomical site of the perforation and eliminate foci of infection.…”
Section: Introductionmentioning
confidence: 99%